Biological Anchorage and Canine Orthodontic Movement Rate with a New Technique for Micro-Osteoperforations - Andrés Arredondo; Daniela Pérez; Oscar Zapata-Noreña; Claudia Ramírez; Álvaro Carvajal-Flórez; Elsa Arango; Diana Barbosa-Liz; Jorge Gil; Paula Duque; Juan Gallego; Catalina Castaño; Sonia Patricia Plaza-Ruíz (Case Reports in Dentistry)
Introduction. The differential management of anchorage and the acceleration of tooth movement are some of the current greatest challenges for orthodontists. Diverse techniques and devices to reinforce anchorage and increase the rate of tooth movement have been proposed. Whether micro-osteoperforations (MOPs) can be used for both purposes is currently investigated. Objectives. To propose and describe a new technique for biological anchorage, which involves six MOPs performed every four weeks, and to present its results in a clinical case of upper premolar extraction. Intervention. In a dental class II patient who met the selection criteria, three MOPs both on the buccal and palatine sides on the intervention side were performed on the extraction area following the protocol described. No MOPs were performed on the control side. The allocation of the intervention was randomised. The MOPs were performed three times at an interval of four weeks. A 0.019×0.025-inch stainless steel wire was activated with calibrated NiTi springs. The three-dimensional movement of the first molars and upper canines was evaluated. In addition, the comfort, periodontal status, and canine root resorption of the patient were evaluated. Results. Clinical and radiographic results suggest that the MOPs had a positive effect in reducing the loss of biological anchorage of the posterior sector and in the rate of canine tooth movement, without damaging changes in the soft and hard tissues. Conclusion. The proposed protocol involving six MOPs every four weeks improved the behaviour of biological anchorage and increased distalization on the intervention side in this clinical case.